Closed-loop deep brain stimulation based on firing-rate regulation - Pasillas-Lepine, William; Haidar, Ihab; Chaillet, Antoine; Panteley, Elena (2013 6th International IEEE/EMBS Conference on Neural Engineering (NER), 2013)
This paper develops a new closed-loop strategy for deep brain stimulation, derived using a model-based analysis of the basal ganglia. The system is described using a firing-rate model that has been proposed recently in the literature, in order to analyze the generation of beta-band oscillations. On this system, a proportional regulation of the firing-rate compensates the loss of stability of the subthalamo-pallidal loop in the parkinsonian case. Nevertheless, because of actuation and measurement delays in the stimulation device, a filter with a well chosen frequency must be added to such proportional schemes, in order to achieve an adequate stability margin.